Method for manufacturing a ceramic preform

CN123022650APending Publication Date: 2026-10-30KURARAY NORITAKE DENTAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580024015.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-28
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

根据本发明,可提供即便在成型体的尺寸大的情况下,也能够通过高升温速度而缩短至预烧结束为止的时间且能够抑制缺损发生的陶瓷预烧体的制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022650A_ABST
    Figure CN123022650A_ABST
Patent Text Reader

Abstract

Provided is a method for producing a ceramic pre-fired body that can shorten the time to the end of pre-firing and suppress the occurrence of defects at a high temperature increase rate. The present invention relates to a method for producing a ceramic pre-fired body, which includes a heat treatment step of heating a molded body of a ceramic, the heat treatment step including a first heat treatment step, and further including a second heat treatment step as necessary, at least one of the first heat treatment step or the second heat treatment step including a step of heating the molded body of the ceramic in an atmosphere having an oxygen partial pressure of 0.11 atm or less, the molded body containing an organic material. The first heat treatment step is a heat treatment step in an atmosphere having an oxygen partial pressure of 0.11 atm or less, and the temperature increase rate in the first heat treatment step is preferably 2.0°C / min or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for manufacturing a ceramic pre-fired body. More specifically, it relates to a method for manufacturing a ceramic pre-fired body with a high heating rate and suppressed occurrence of defects such as breakage or cracks. Background Technology

[0002] Oxide ceramics are widely used in industry. Among them, zirconia sintered bodies have been used in recent years for dental materials such as dental repairs. These dental repairs are generally manufactured as follows: zirconia particles are press-molded or formed using a composition containing zirconia particles to create a zirconia molded body with a desired shape such as a disc or prism; this is then pre-fired to create a pre-fired body (grind blank); this pre-fired body is then cut (milled) into the target shape of the dental repair and further sintered.

[0003] A commonly known method for manufacturing pre-fired ceramic bodies is to burn off the organic binder contained in the ceramic molded body and heat it to a specified temperature.

[0004] The process of removing the aforementioned organic binder (hereinafter also referred to as the "degreasing process") is mostly carried out by heating the molded body in air to a temperature above which the aforementioned organic binder decomposes.

[0005] On the other hand, in order to suppress the occurrence of defects such as cracking and gaps during the heat treatment of the molded body, a method of heating to a specified temperature in an inactive atmosphere has been proposed (for example, Patent Document 1).

[0006] In addition, when a pre-fired body (semi-sintered body) manufactured by heating the molded body under atmospheric conditions and at a specified temperature is sintered to manufacture a sintered body after machining the pre-fired body, defects such as cracks and gaps may occur in the sintered body. Therefore, in order to suppress the occurrence of such defects, a method has been proposed that includes a pre-firing process in which the body is heated and held in an inactive atmosphere or a reducing atmosphere, and then pre-fired in an active atmosphere or a reducing atmosphere (Patent Document 2).

[0007] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 49-074705 Patent Document 2: Japanese Patent Application Publication No. 2013-119485. Summary of the Invention

[0008] The problem the invention aims to solve According to the inventor's research, Patent Document 1 does not disclose any specific details about organic binders other than NEOPRENE (registered trademark) (chloroprene rubber) binders. Furthermore, its content is not disclosed, and the heating rate is approximately 1.5°C / minute.

[0009] Furthermore, Patent Document 1 only discloses that ceramic structures containing organic binders are extremely difficult to suppress during sintering due to their structural characteristics, resulting in defects such as cracks and gaps. It is extremely difficult to suppress defects caused by organic binders alone. Therefore, it does not provide any guidance on how to shorten the sintering process.

[0010] Therefore, Patent Document 1 does not disclose the ability to shorten the time from the start of heating to the end of pre-firing (the time from the start of heating to the end of the holding time at the highest temperature of the pre-firing process) by setting a high heating rate, nor does it disclose the ability to suppress defects such as cracks and gaps.

[0011] Furthermore, Patent Document 2 also did not suggest a shorter timeframe.

[0012] In the prior art, if the heating rate is drastically increased before degreasing the molded body containing organic binder, defects such as cracking and gaps will occur. Therefore, when degreasing and pre-firing are taken into account, it is difficult to simultaneously reduce the time from the start of heating to the end of pre-firing (the time from the start of heating to the end of the holding time at the highest temperature of the pre-firing process) caused by the high heating rate, as well as suppress the occurrence of defects such as cracking and gaps.

[0013] The purpose of this invention is to provide a method for manufacturing a ceramic pre-fired body that can shorten the time to the end of pre-firing by using a high heating rate and can suppress the occurrence of defects.

[0014] Methods for solving problems In order to solve the above-mentioned problems, the inventors have repeatedly conducted in-depth research and found that by a heat treatment process including heating a ceramic molded body, the heat treatment process including a first heat treatment process and a second heat treatment process, wherein at least one of the first heat treatment process or the second heat treatment process includes heating the ceramic molded body in an atmosphere with an oxygen partial pressure of less than 0.11 atm, and wherein the molded body contains organic materials, it is possible to achieve both high heating rate and suppression of defects. Based on this insight, further research was conducted, thereby completing the present invention.

[0015] The present invention includes the following technical solutions.

[0016] [1] A method for manufacturing a pre-fired ceramic body, comprising a heat treatment step of heating a shaped ceramic body. The aforementioned heat treatment process includes a first heat treatment process, and may further include a second heat treatment process as needed. At least one of the aforementioned first heat treatment step or the aforementioned second heat treatment step includes a step of heating the ceramic molded body in an atmosphere with an oxygen partial pressure of less than 0.11 atm. The aforementioned molded body contains organic materials.

[0017] [2] According to the method for manufacturing the ceramic pre-fired body described in [1], the aforementioned first heat treatment step is a heat treatment step in an atmosphere with an oxygen partial pressure of 0.11 atm or less. The heating rate in the aforementioned first heat treatment process is 2.0℃ / minute or higher.

[0018] [3] The method for manufacturing a ceramic pre-fired body according to [2] further includes, after the first heat treatment step, a pre-firing step of heating the aforementioned molded body in an atmosphere with an oxygen partial pressure of 0.12 atm or higher and maintaining a maximum temperature of 800°C or higher and 1300°C or lower.

[0019] [4] According to the method for manufacturing a ceramic pre-fired body described in [3], the aforementioned second heat treatment step is performed after the aforementioned first heat treatment step and before the aforementioned pre-firing step. In the aforementioned second heat treatment process, the aforementioned molded body is heated in an atmosphere with an oxygen partial pressure of 0.12 atm or higher.

[0020] [5] According to the method for manufacturing the ceramic pre-fired body described in [4], the heating rate in the aforementioned second heat treatment step is 2.0°C / min or higher.

[0021] [6] The method for manufacturing a ceramic pre-fired body according to [4] or [5], wherein the temperature range in the aforementioned second heat treatment step is above 500°C and below 1300°C.

[0022] [7] The method for manufacturing a ceramic pre-fired body according to [4] or [5] further includes a holding step of heating the aforementioned molded body by holding it at a constant temperature in the range of 500°C or higher and 1300°C or lower.

[0023] [8] The method for manufacturing a ceramic pre-fired body according to any one of [1] to [5], wherein the aforementioned organic material comprises an acrylic binder.

[0024] [9] According to the method for manufacturing the ceramic pre-fired body described in [8], the content of the aforementioned organic material is 1 to 12% of the total mass of the ceramic molded body in 100% by mass.

[0025]

[10] The method for manufacturing a ceramic pre-fired body according to any one of [1] to [9], wherein the aforementioned molded body has a diameter of more than 2.7 cm. 3 A rectangular parallelepiped with a volume and thickness exceeding 1 cm, or having a diameter exceeding 19.0 cm. 3 It is a disc-shaped object with a volume and a thickness of more than 1 cm.

[0026]

[11] The method for manufacturing a ceramic pre-fired body according to any one of [1] to

[10] , wherein the ceramic comprises zirconium oxide and a stabilizer capable of suppressing the zirconium oxide phase transformation, wherein the zirconium oxide comprises monoclinic zirconium oxide as the main component.

[0027]

[12] According to the method for manufacturing the ceramic pre-fired body described in

[11] , the stabilizer that can suppress the zirconium oxide phase transformation is yttrium oxide, and the ceramic contains yttrium oxide that is not dissolved in zirconium oxide.

[0028]

[13] The method for manufacturing a ceramic pre-fired body according to any one of [1] to

[12] , wherein the ceramic further comprises TiO2.

[0029]

[14] The method for manufacturing a ceramic pre-fired body according to any one of [1] to

[13] , wherein the ceramic further comprises Nb2O5.

[0030]

[15] The method for manufacturing a ceramic pre-fired body according to any one of [3] to

[14] , wherein the time of the aforementioned pre-firing process is in the range of 1 minute to 1 hour.

[0031]

[16] The method for manufacturing a ceramic pre-fired body according to any one of [3] to

[15] , wherein the total time from the start of the first heat treatment step to the end of the holding time at the highest temperature of the pre-fired step is less than 600 minutes.

[0032]

[17] The method for manufacturing a ceramic pre-fired body according to any one of [3] to

[16] , wherein the aforementioned ceramic pre-fired body is used to manufacture dental repairs.

[0033]

[18] A method for manufacturing a ceramic sintered body, comprising: a sintering step of sintering a pre-sintered ceramic body obtained by any one of the manufacturing methods of [1] to

[17] at a temperature with a maximum calcination temperature exceeding 1200°C.

[0034] Invention Effects According to the present invention, a method for manufacturing a ceramic pre-fired body can be provided, which can shorten the time to the end of pre-firing by means of a high heating rate and suppress the occurrence of defects, even when the size of the molded body is large.

[0035] According to the present invention, the time from the start of heating to the end of preheating can be shortened, thus significantly reducing the manufacturing process, which is industrially advantageous.

[0036] Furthermore, according to the present invention, a method for manufacturing a ceramic pre-fired body can be provided that, even when the size of the molded body is large, the time to the end of pre-firing can be shortened by a high heating rate and the occurrence of defects can be suppressed. Attached Figure Description

[0037] Figure 1 This is a graph showing the temperature and oxygen concentration changes in Example 1. Detailed Implementation

[0038] The method for manufacturing the ceramic pre-fired body of the present invention includes a heat treatment step of heating the ceramic molded body. The aforementioned heat treatment process includes a first heat treatment process, and may further include a second heat treatment process as needed. At least one of the aforementioned first heat treatment step or the aforementioned second heat treatment step includes a step of heating the ceramic molded body in an atmosphere with an oxygen partial pressure of less than 0.11 atm. The aforementioned molded body contains organic materials.

[0039] As a suitable embodiment of the present invention, the following method for manufacturing a pre-fired ceramic body includes a heat treatment step of heating a shaped ceramic body. The aforementioned heat treatment process includes a first heat treatment process and a second heat treatment process. At least one of the aforementioned first heat treatment step or the aforementioned second heat treatment step includes a step of heating the ceramic molded body in an atmosphere with an oxygen partial pressure of less than 0.11 atm. The aforementioned molded body contains organic materials.

[0040] As other suitable embodiments, the following methods for manufacturing pre-fired ceramic bodies include a heat treatment step of heating a shaped ceramic body. The aforementioned heat treatment process includes a first heat treatment process. The aforementioned first heat treatment process includes heating the ceramic molded body in an atmosphere with an oxygen partial pressure below 0.11 atm. The aforementioned molded body contains organic materials.

[0041] In this specification, "molded body" refers to any object that has not reached the semi-sintered state (pre-sintered state) or the sintered state. That is, a molded body is distinguished from a pre-sintered body and a sintered body in that it has not been calcined after being formed into a molded body.

[0042] In this specification, "pre-fired body" refers to a semi-sintered state in which ceramic particles are necked (fixed) together, but the ceramic particles (e.g., zirconia particles) have not yet been fully sintered.

[0043] In this specification, "sintered body" refers to the sintered state of ceramic particles (such as zirconia particles) that are completely sintered.

[0044] In this specification, "the highest temperature of the pre-firing process" refers to the heating temperature that is finally reached and maintained for a specified time in the pre-firing process (the calcination process used to obtain the pre-fired body).

[0045] In this specification, "maximum calcination temperature" refers to the heating temperature that is finally reached and maintained for a specified time in the sintering process (the calcination process used to obtain the sintered body).

[0046] In this specification, the content (mol%) of the stabilizer capable of suppressing the zirconium oxide phase transformation refers to the content calculated by converting zirconium oxide and the aforementioned stabilizer into oxides.

[0047] In addition, in this instruction manual, "end of pre-firing" means that the holding time at the highest temperature in the pre-firing process has ended.

[0048] In this specification, "holding" a specific temperature also includes situations where the temperature changes within the range of the upper and lower limits of the specific temperature (e.g., -15°C to +15°C). For example, during preheating at 1000°C, the temperature can change from 985°C to 1015°C until the end of the holding time.

[0049] In this specification, "zirconia" refers to zirconia (IV) (ZrO2), and ZrO2 particles contain trace amounts (more than 0.5% by mass and less than 3% by mass) of HfO2 relative to ZrO2. HfO2 is difficult to separate; therefore, terms such as "zirconia," "zirconia particles," and "zirconia powder" refer to particles containing both ZrO2 and HfO2. Furthermore, particles and powders formed by the solidification of stabilizers in zirconia are also included in "zirconia particles" and "zirconia powder," respectively.

[0050] In this specification, "first heat treatment process" refers to the initial heating process in which the ceramic molded body is heated.

[0051] In this specification, "second heat treatment process" refers to a heating process that is performed after the first heat treatment process and before the pre-firing process to heat the ceramic molded body, and it refers to a heating process in which at least one of the atmospheric gas conditions (type of atmospheric gas, pressure, concentration, etc.) is different from that of the first heat treatment process.

[0052] In this instruction manual, "atmospheric" refers to standard atmospheric pressure (1 atm).

[0053] It should be noted that the upper and lower limits of the numerical ranges (temperature range, volume, thickness, oxygen partial pressure, oxygen concentration, ratio of heating rate to oxygen partial pressure (heating rate / oxygen partial pressure), content of each component, values ​​calculated from the components, and various physical properties, etc.) in this specification can be appropriately combined.

[0054] The following description uses the manufacturing method of a ceramic pre-fired body, which includes the first heat treatment step and the second heat treatment step, as an example. However, the second heat treatment step is not necessary, and therefore, it is not limited to including the second heat treatment step.

[0055] In the method for manufacturing the ceramic pre-fired body of the present invention, at least one of the first heat treatment step or the second heat treatment step has an oxygen partial pressure of 0.11 atm or less.

[0056] From the viewpoint that the occurrence of defects can be further suppressed by combining with other components (such as acrylic binders) and that the time to the end of pre-firing can be shortened by a high heating rate, the aforementioned oxygen partial pressure is preferably 0.10 atm or less, more preferably 0.02 atm or less, even more preferably 0.01 atm or less, and particularly preferably 0.008 atm or less.

[0057] In addition, the aforementioned oxygen partial pressure is not specifically limited and can exceed 0 atm.

[0058] As a suitable embodiment, a method for manufacturing a ceramic pre-fired body can be cited, wherein the oxygen partial pressure in the first heat treatment step is 0.11 atm or less.

[0059] As another suitable implementation, a method for manufacturing a ceramic pre-fired body can be listed, wherein the oxygen partial pressure in the second heat treatment step is 0.11 atm or less.

[0060] As another suitable embodiment, a method for manufacturing a ceramic pre-fired body can be cited, wherein the oxygen partial pressure in the first heat treatment step and the second heat treatment step is 0.11 atm or less.

[0061] The oxygen partial pressures in the first and second heat treatment processes can be appropriately selected within the range specified in this specification, and can be either the same or different from each other.

[0062] For example, when the oxygen partial pressure in both the first heat treatment step and the second heat treatment step is 0.11 atm or less, a method for manufacturing a ceramic pre-fired body can be listed, wherein the oxygen partial pressure in the aforementioned first heat treatment step is 0.02 atm or less, and the oxygen partial pressure in the second heat treatment step is more than 0 atm but less than 0.11 atm.

[0063] In this specification, as long as the effects of the present invention can be obtained, the description of the heating rate, etc., can be applied to any embodiment, unless otherwise stated.

[0064] The heating rate in the first heat treatment step is preferably 2.0℃ / min or more, more preferably 5.0℃ / min or more, further preferably 10℃ / min or more, particularly preferably 15℃ / min or more, and most preferably 20℃ / min or more.

[0065] The heating rate in the first heat treatment step is preferably 1000°C / min or less, more preferably 800°C / min or less, and even more preferably 500°C / min or less.

[0066] In other words, the heating rate in the first heat treatment process is preferably 2.0~1000℃ / min, more preferably 5.0~800℃ / min, even more preferably 10~500℃ / min, particularly preferably 15~500℃ / min, and most preferably 20~500℃ / min.

[0067] The heating rate in the first heat treatment step can be a constant rate or can be varied within the aforementioned range. For example, in the first heat treatment step, if the rate is 5.0°C / minute or higher, an embodiment is also included in which the heating rate starts at 5.0°C / minute and is then changed to 50°C / minute during the process.

[0068] The first heat treatment process is a heating process, which can be referred to as the first heating process.

[0069] As a suitable embodiment, a method for manufacturing a ceramic pre-fired body can be listed, wherein the first heat treatment step is a heat treatment step in an atmosphere with an oxygen partial pressure of 0.11 atm or less, and the heating rate in the first heat treatment step is 2.0°C / min or more.

[0070] In the method for manufacturing the ceramic pre-fired body of the present invention, by including at least one of the first heat treatment step or the second heat treatment step in a step of heating the ceramic molded body in an atmosphere with an oxygen partial pressure of 0.11 atm or less, the heating rate can be increased and the occurrence of defects can be suppressed.

[0071] The reason why heating the ceramic molded body in at least one of the first heat treatment process or the second heat treatment process in an atmosphere with an oxygen partial pressure of less than 0.11 atm can increase the heating rate and suppress the occurrence of defects is still uncertain, but it can be considered as follows.

[0072] It can be considered that in at least one of the first heat treatment process or the second heat treatment process, by increasing the heating rate in an atmosphere with an oxygen partial pressure of less than 0.11 atm, the organic material contained in the molded body is decomposed by heating, and carbonization is carried out slowly over a wide temperature range. This can suppress the rapid generation of decomposition gases during the decomposition of organic materials. Therefore, it can avoid a sharp increase in the amount of decomposition gases and cracks in the molded body when a specific temperature is reached.

[0073] In the method for manufacturing the ceramic pre-fired body of the present invention, at least one of the first heat treatment step or the second heat treatment step includes a step of heating the ceramic molded body in an atmosphere with an oxygen partial pressure of less than 0.11 atm.

[0074] Atmospheres with an oxygen partial pressure below 0.11 atm can include inactive atmospheres, reducing atmospheres, depressurized atmospheres, and vacuum atmospheres.

[0075] Examples of inactive gases used to create inactive atmospheres include helium, neon, argon, krypton, xenon, radon, nitrogen (N2 gas), carbon dioxide (CO2 gas), and non-flammable fluorocarbon gases.

[0076] Examples of reducing gases used to create a reducing atmosphere include H2 gas, hydrogen sulfide gas, ammonia decomposition gas, H2 (Ar / H2) diluted with an inactive gas, or carbon monoxide (CO), carbon monoxide (CO) diluted with nitrogen (N2), etc.

[0077] The reduced pressure atmosphere and vacuum atmosphere can be set using known methods and apparatus without particular limitations.

[0078] In addition, the oxygen concentration in the first heat treatment process is preferably 10% or less. When the size of the molded body is large, from the viewpoint that the occurrence of defects can be suppressed and the time until the end of pre-firing can be shortened by the high heating rate, it is more preferably 5% or less, further preferably 3% or less, particularly preferably less than 1%, and most preferably less than 0.5%.

[0079] In one suitable embodiment, a method for manufacturing a ceramic pre-fired body can be listed, wherein the oxygen concentration in the first heat treatment step is 0.3% or less.

[0080] The method for determining oxygen concentration is as described in the examples described later.

[0081] The starting temperature in the first heat treatment process is not particularly limited; it can be room temperature or 0°C.

[0082] The preferred temperature for the first heat treatment step is 600°C, more preferably 550°C, and even more preferably 500°C.

[0083] Furthermore, in at least one of the aforementioned first heat treatment step or the aforementioned second heat treatment step, from the viewpoint that the heating rate can be increased to shorten the time until the pre-firing is completed, and that the molding body can be more effectively suppressed from breaking by combining with other components (such as acrylic binders), the ratio of heating rate to oxygen partial pressure (heating rate / oxygen partial pressure) is preferably 7°C / (atm·min) or more, more preferably 15°C / (atm·min) or more, further preferably 100°C / (atm·min) or more, and particularly preferably 800°C / (atm·min) or more.

[0084] Furthermore, from the viewpoint that the heating rate can be increased to shorten the time until the pre-firing is completed, and that by combining with other components (such as acrylic binders) the breakage of the molded article can be more effectively suppressed, the ratio of heating rate to oxygen partial pressure (heating rate / oxygen partial pressure) is preferably less than 500,000 °C / (atm·min), more preferably 400,000 °C / (atm·min) or less, even more preferably 200,000 °C / (atm·min) or less, and particularly preferably 120,000 °C / (atm·min) or less.

[0085] In other words, the ratio of heating rate to oxygen partial pressure (heating rate / oxygen partial pressure) is preferably 7°C / (atm·min) or more and less than 500,000°C / (atm·min), more preferably 15°C / (atm·min) or more and less than 400,000°C / (atm·min), further preferably 100°C / (atm·min) or more and less than 200,000°C / (atm·min), and particularly preferably 800°C / (atm·min) or more and less than 120,000°C / (atm·min).

[0086] The ceramic molded body contains organic materials. Examples of such organic materials include methacrylic binders and acrylic binders. From the viewpoints of excellent moldability and debinding speed, and from the viewpoints of effectively suppressing gas generation and molded body breakage caused by violent combustion due to rapid heating when combined with other components, acrylic binders are preferred.

[0087] The content of organic material contained in the molded body is preferably 12% or less out of 100% of the total mass of the ceramic molded body. When the size of the molded body is large, from the viewpoint that defects can be suppressed and the time to the end of pre-firing can be shortened by a high heating rate, it is more preferably 10% or less out of mass, further preferably 8% or less out of mass, and particularly preferably 6% or less out of mass.

[0088] Furthermore, the content of organic material is preferably 1% by mass or more. When the size of the molded body is large, from the viewpoint that defects can be suppressed and the time to the end of pre-firing can be shortened by a high heating rate, it is more preferably 1.2% by mass or more, even more preferably 1.5% by mass or more, and particularly preferably 2% by mass or more.

[0089] In other words, the content of organic materials is preferably 1% or more and 12% or less by mass, more preferably 1.2% or more and 10% or less by mass, even more preferably 1.5% or more and 8% or less by mass, and particularly preferably 2% or more and 6% or less by mass.

[0090] There are no particular restrictions on the shape of the molded object; examples include cuboids, discs, etc.

[0091] Regarding the size of the molded body, from the viewpoint of easily manufacturing dental restorations that correspond to one natural tooth, the molded body is preferably larger than 2.7 cm. 3 A rectangular parallelepiped with a volume and thickness exceeding 1 cm, or having a diameter exceeding 19.0 cm. 3 It is a disc-shaped object with a volume and thickness exceeding 1 cm.

[0092] In the case of a rectangular parallelepiped-shaped molded body, a volume of 3 cm is more preferable. 3 The above is further preferred to be 5cm. 3 That's all. There are no specific volume restrictions; it can be set to 125cm. 3 the following.

[0093] In the case of a rectangular parallelepiped, a thickness of 1.2 cm or more is preferred, and 1.5 cm or more is even more preferred. The thickness is not particularly limited and can be 5 cm or less.

[0094] In this specification, "disc-shaped" includes not only circles, but also flat shapes such as ellipses that are surrounded by closed curves.

[0095] In this specification, "cuboid" refers to a solid shape that is usually composed of 6 rectangular faces, and also includes cases where each ridge and / or vertex is composed of curved surfaces, that is, with arcs (e.g., shapes with rounded corners or R-shaped treatment).

[0096] Ceramic materials used as molded bodies include alumina, zirconium oxide, etc., with zirconium oxide being a preferred main component.

[0097] "Containing zirconium oxide as a main component" means that the zirconium oxide content in the ceramic is 50% by mass or more, preferably 55% by mass, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more.

[0098] Zirconia can be used in any crystal system, including monoclinic, tetragonal, and cubic systems.

[0099] As a suitable embodiment, a method for manufacturing a ceramic pre-fired body can be listed, wherein the ceramic comprises zirconium oxide and a stabilizer capable of inhibiting the zirconium oxide phase transformation, wherein the zirconium oxide comprises monoclinic zirconium oxide as the main component.

[0100] When using alumina as the ceramic, the molded body may also be free of the "stabilizer that can inhibit the zirconium oxide phase transformation" described later.

[0101] "Including monoclinic zirconium oxide as the main component" means that in the zirconium oxide in ceramics, the proportion f of monoclinic zirconium oxide as shown in the following formula (1) is... m It is over 50%.

[0102] f m =I 28 / (I 28 +I 30 )×100 (1) (where f) m The percentage (%) of monoclinic crystals is represented by I in XRD measurements. 28 I represents the area intensity of the peak near 2θ=28°, which is the main peak of the monoclinic crystal system. 30 This represents the area intensity of the peak near 2θ=30°, which is the main peak observed in tetragonal or cubic crystal systems.

[0103] As for the proportion of monoclinic zirconium oxide shown in formula (1), when manufacturing a sintered body, even if the holding time is short at the highest calcination temperature, from the viewpoint of excellent light transmittance, it is preferably 55% or more, more preferably 80% or more, further preferably 85% or more, and particularly preferably 90% or more.

[0104] When the ceramic of the molded article contains zirconium oxide as the main component, it is preferable to also contain a stabilizer (hereinafter referred to as "stabilizer") that can suppress the zirconium oxide phase transformation.

[0105] Examples of stabilizers capable of suppressing the zirconium oxide phase transformation include calcium oxide (CaO), magnesium oxide (MgO), yttrium oxide (Y₂O₃), cerium oxide (CeO₂), scandium oxide (Sc₂O₃), niobium oxide (Nb₂O₅), lanthanum oxide (La₂O₃), erbium oxide (Er₂O₃), and praseodymium oxide (Pr₂O₃, Pr₆O₃). 11Oxides such as samarium oxide (Sm₂O₃), europium oxide (Eu₂O₃), thulium oxide (Tm₂O₃), gallium oxide (Ga₂O₃), indium oxide (In₂O₃), and ytterbium oxide (Yb₂O₃) are preferred, from the viewpoint of superior performance, especially aesthetics. Y₂O₃ (yttrium oxide) and / or CeO₂ are preferred. One of the aforementioned stabilizers may be used alone, or two or more may be used in combination.

[0106] The content of stabilizer relative to the total mol of zirconium oxide (zirconia (IV); ZrO2) and stabilizer is preferably 2 mol% or more, more preferably 3 mol% or more, even more preferably 3.5 mol% or more, and particularly preferably 4 mol% or more. When it is 2 mol% or more, it is preferred from the viewpoint that the cubic crystal system in the sintered body increases and the light transmittance is improved.

[0107] Furthermore, the content of the aforementioned stabilizer is preferably 9 mol% or less, more preferably 8.5 mol% or less, even more preferably 8 mol% or less, and particularly preferably 7.5 mol% or less. When the content is 9 mol% or less, the proportion of cubic crystals in the contained crystal system is not excessive, which easily suppresses grain growth, prevents the crystal structure from becoming too large, and suppresses the decrease in light transmittance; therefore, it is preferred.

[0108] The content of the aforementioned stabilizers can be set to a range achieved by any combination thereof. For example, the content of the aforementioned stabilizers is preferably 2 to 9 mol%, more preferably 3 to 8.5 mol%, even more preferably 3.5 to 8 mol%, and particularly preferably 4 to 7.5 mol%. The content of the aforementioned stabilizers can be set to a range of 3.7 to 8 mol% as needed.

[0109] The content of stabilizers in the aforementioned molded body can be quantified using common analytical methods. Examples include inductively coupled plasma (ICP) luminescence spectrophotometry, fluorescence X-ray analysis (XRF), and energy-dispersive or wavelength-dispersive X-ray analysis (SEM-EDX or SEM-WDX) attached to a scanning electron microscope.

[0110] In addition, as a suitable embodiment, a method for manufacturing a ceramic pre-fired body can be listed, wherein the stabilizer capable of suppressing the zirconium oxide phase transformation is yttrium oxide, and the ceramic comprises zirconium oxide and yttrium oxide not dissolved in zirconium oxide.

[0111] The presence rate f of yttrium oxide not dissolved in zirconium oxide (hereinafter also referred to as "undissolved yttrium oxide") y It can be calculated according to the following mathematical formula (2).

[0112] f y =I 29 / (I28 +I 29 +I 30 )×100 (2) (where f) y The percentage of unsolvated yttrium oxide (%) is represented by I in XRD measurements. 28 I represents the area intensity of the peak near 2θ=28°, which is the main peak of the monoclinic crystal system. 29 I represents the area intensity of the peak near 2θ=29°, which is the main peak of yttrium oxide. 30 This represents the area intensity of the peak near 2θ=30°, which is the main peak observed in tetragonal or cubic crystal systems.

[0113] From the perspective of easily obtaining the target sintered zirconia, the presence rate f of undissolved yttrium oxide is... y Preferably greater than 0%, more preferably 1% or more, further preferably 2% or more, and particularly preferably 3% or more. The presence rate of undissolved yttrium oxide f y The upper limit can be, for example, below 25%, depending on the yttrium oxide content in the raw material composition or the molded body.

[0114] For example, when the content of yttrium oxide in the molded body of the present invention or the raw material composition for manufacturing the molded body (hereinafter also referred to as the "raw material composition") is 3 mol% or more and 8 mol% or less, the following is true.

[0115] When the yttrium oxide content is above 3 mol% and below 4.5 mol%, f y It can be set to below 15%. When the yttrium oxide content is above 4.5 mol% and below 5.8 mol%, f y It can be set below 20%. When the yttrium oxide content is above 5.8 mol% and below 8 mol%, f y It can be set to below 25%.

[0116] For example, when the yttrium oxide content is above 3 mol% and below 4.5 mol%, f y Preferably, it is 2% or more, more preferably 3% or more, even more preferably 4% or more, and particularly preferably 5% or more.

[0117] In other words, when the yttrium oxide content is above 3 mol% and below 4.5 mol%, f y Preferably, it is 2% or more and 15% or less, more preferably 3% or more and 15% or less, even more preferably 4% or more and 15% or less, and particularly preferably 5% or more and 15% or less.

[0118] When the yttrium oxide content is above 4.5 mol% and below 5.8 mol%, f yPreferably, it is 3% or more, more preferably 4% or more, even more preferably 5% or more, even more preferably 6% or more, and particularly preferably 7% or more.

[0119] In other words, when the yttrium oxide content is above 4.5 mol% and below 5.8 mol%, f y Preferably, it is 3% or more and 20% or less, more preferably 4% or more and 20% or less, even more preferably 5% or more and 20% or less, even more preferably 6% or more and 20% or less, and particularly preferably 7% or more and 20% or less.

[0120] When the yttrium oxide content is above 5.8 mol% and below 8 mol%, f y Preferably, it is 4% or more, more preferably 5% or more, even more preferably 6% or more, even more preferably 7% or more, and particularly preferably 8% or more.

[0121] In other words, when the yttrium oxide content is above 5.8 mol% and below 8 mol%, f y Preferably, it is 4% or more and 25% or less, more preferably 5% or more and 25% or less, even more preferably 6% or more and 25% or less, even more preferably 7% or more and 25% or less, and particularly preferably 8% or more and 25% or less.

[0122] In the molded article or raw material composition of the present invention, not all of the stabilizer may be completely dissolved in ZrO2 and HfO2. It should be noted that, in this specification, "stabilizer is dissolved" means, for example, that elements (atoms) contained in the stabilizer are dissolved in ZrO2 and HfO2.

[0123] From a machinability point of view, the ceramic molded body may also contain Nb2O5.

[0124] As another suitable embodiment, a method for manufacturing a pre-fired ceramic body can be cited, wherein the shaped ceramic body comprises zirconium oxide, a stabilizer capable of inhibiting the zirconium oxide phase transformation, and an organic material, and includes Nb2O5 and / or Ta2O5. In a total of 100 mol% of zirconium oxide, the aforementioned stabilizer, Nb₂O₅, and Ta₂O₅, The content of zirconium oxide (total content of ZrO2 and HfO2) is 78~97.5 mol%. The aforementioned stabilizer contains 1-12 mol%. The combined content of Nb₂O₅ and Ta₂O₅ is 1~9 mol%. It also includes elements of family I.

[0125] In the aforementioned embodiments, the zirconia sintered body (hereinafter referred to as "zirconia composite sintered body") obtained by sintering the pre-sintered body can also be machined in the sintered state, exhibiting excellent machinability.

[0126] The content (mol%) of Group I elements in the molded body is the external addition rate relative to the total 100 mol% of zirconium oxide, the aforementioned stabilizer, Nb₂O₅, and Ta₂O₅. The content of Group I elements is calculated by converting the amount (mass) of raw materials added at the time of addition into mol%.

[0127] The reason why the zirconia composite sintered body can be machined in the sintered state in the aforementioned embodiments is still uncertain, but the following speculation is made.

[0128] It can be inferred that in a zirconia composite sintered body containing zirconia and a stabilizer that can inhibit the zirconia phase transformation and containing Nb2O5 and / or Ta2O5, the presence of Group I elements at the interface of zirconia particles (hereinafter also referred to as "grain boundaries") reduces the grain boundary strength and acts in a direction that makes the particles easier to separate from each other, thus improving machinability.

[0129] Furthermore, regarding Nb₂O₅ and / or Ta₂O₅, in the zirconia composite sintered body, the fine structure coarsens, contributing to a decrease in hardness. Therefore, Group I elements integrate with Nb₂O₅ and / or Ta₂O₅, improving machinability. Consequently, Group I elements, integrated with Nb₂O₅ and / or Ta₂O₅, provide the necessary strength for artificial teeth and impart excellent free-machining properties.

[0130] Group I elements include Li, Na, K, Rb, Cs, and Fr. A single Group I element can be used, or two or more can be used in combination.

[0131] The content of Group I elements in the molded article is preferably more than 0 mol% and less than 5.0 mol%. From the viewpoint of better machinability, it is more preferably 0.05 mol% or more and less than 4.0 mol%. From the viewpoint of better strength, it is even more preferably 0.06 mol% or more and less than 3.0 mol%. It is particularly preferably 0.07 mol% or more and less than 1.0 mol%. It is most preferably 0.08 mol% or more and less than 0.34 mol%.

[0132] The aforementioned content rate can be used as long as it is a Group I element.

[0133] On the other hand, compared to Li and Na, K, Rb, Cs, and Fr have higher atomic weights. As the atomic weight increases, the forces acting in the direction that facilitates the separation of particles from each other increase, leading to a tendency for the required content to decrease in order to achieve the effects of this invention. Therefore, when the Group I elements are K, Rb, Cs, and Fr, a smaller content range can be selected (e.g., 0.05 mol% or more and 1.0 mol% or less), and when the Group I elements are Li and / or Na, a larger content range can be selected (e.g., 0.08 mol% or more and 3.0 mol% or less).

[0134] The zirconium oxide content in the molded article is 78 to 97.5 mol% in a total of 100 mol% of zirconium oxide, the aforementioned stabilizer, Nb2O5 and Ta2O5. From the viewpoint of superior light transmittance and strength, it is preferably 79 mol% or more and 96 mol% or less, more preferably 80 mol% or more and 94 mol% or less, and even more preferably 81 mol% or more and 93 mol% or less.

[0135] The content of stabilizer in the molded body is preferably 2 mol% or more and 10 mol% or less in the total of 100 mol% of zirconium oxide, the aforementioned stabilizer, Nb2O5 and Ta2O5. From the viewpoint of better light transmittance and strength, it is more preferably 3 mol% or more and 8 mol% or less, and even more preferably 3.5 mol% or more and 7.5 mol% or less.

[0136] When manufacturing a zirconia composite sintered body that can be machined even in the sintered state, the total content of Nb2O5 and Ta2O5 in the molded body is 1 to 9 mol% of the total 100 mol% of zirconia, the aforementioned stabilizer, Nb2O5 and Ta2O5, preferably 1.5 mol% or more and 8.5 mol% or less. From the viewpoint of working together with Group I elements and having better machinability, it is more preferably 2.5 mol% or more and 8 mol% or less, and even more preferably 3 mol% or more and 7 mol% or less.

[0137] When the combined content of Nb₂O₅ and Ta₂O₅ is 1 mol% or more, sufficient machinability is easily obtained. Furthermore, when the combined content of Nb₂O₅ and Ta₂O₅ is 9 mol% or less, it is easier to suppress notches and other defects in the resulting zirconia composite sintered body, thus easily obtaining sufficient physical properties.

[0138] The molded body used to obtain the aforementioned zirconia composite sintered body may also contain TiO2.

[0139] The TiO2 content is preferably more than 0% and less than 5.0% by mass relative to the total mass% of zirconium oxide, the aforementioned stabilizer, Nb2O5 and Ta2O5 (100% by mass), more preferably more than 0.01% by mass and less than 4.5% by mass. From the viewpoint that it can function as a whole when combined with Group I elements and has better strength, it is further preferably more than 0.6% by mass and less than 4.3% by mass, particularly preferably more than 0.7% by mass and less than 3.7% by mass, and most preferably more than 2.5% by mass and less than 3.5% by mass.

[0140] The TiO2 content (mass%) is the external addition rate relative to the total mass% of zirconium oxide, the aforementioned stabilizer, Nb2O5, and Ta2O5. The TiO2 content can be calculated based on the amount (mass) of raw materials added at the time of addition.

[0141] The contents of zirconium oxide, stabilizer, Nb2O5 and Ta2O5, Group I elements and TiO2 in the aforementioned molded body are the same in the pre-fired body and sintered body.

[0142] The molded articles of the present invention may, as needed, contain colorants (including pigments, composite pigments, and fluorescent agents), alumina (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), and other additives (excluding the aforementioned stabilizers). These components may be used individually or in combination of two or more.

[0143] In one suitable embodiment, a method for manufacturing a ceramic pre-fired body may be provided, wherein the ceramic pre-fired body further comprises TiO2.

[0144] As the aforementioned pigments, examples include oxides of at least one element selected from Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Sm, Eu, Gd, and Er (excluding Y2O3 and CeO2).

[0145] Examples of the aforementioned composite pigments include (Zr,V)O2, Fe(Fe,Cr)2O4, (Ni,Co,Fe)(Fe,Cr)2O4・ZrSiO4, and (Co,Zn)Al2O4.

[0146] The molded body of the present invention may contain a fluorescent agent. By including a fluorescent agent in the molded body, the pre-fired body and the sintered body acquire fluorescent properties.

[0147] The type of fluorescent agent is not particularly limited, and one or more fluorescent agents capable of emitting fluorescence using light of any wavelength can be used. Examples of fluorescent agents include those containing a metal element. Examples of such metal elements include Ga, Bi, Ce, Nd, Sm, Eu, Gd, Tb, Dy, and Tm. The fluorescent agent may contain one or more of these metal elements. Among these metal elements, Ga, Bi, Eu, Gd, and Tm are preferred, and Bi and Eu are more preferred. Examples of fluorescent agents include oxides, hydroxides, acetates, and nitrates of the aforementioned metal elements.

[0148] Alternatively, fluorescent agents can be Y₂SiO₅:Ce, Y₂SiO₅:Tb, (Y,Gd,Eu)BO₃, Y₂O₃:Eu, YAG:Ce, ZnGa₂O₄:Zn, ZnGa₂O₄:Mn, BaMgAl 10 O 17 Eu et al.

[0149] The content of fluorescent agent in the molded body is not particularly limited and can be appropriately adjusted according to the type of fluorescent agent or the intended use of the sintered body. From the viewpoint of preferably using it as a dental patch, the content is preferably 0.001% by mass or more, more preferably 0.005% by mass or more, and even more preferably 0.01% by mass or more, relative to 100% by mass of zirconium oxide contained in the molded body, calculated based on the oxide of the metal element contained in the fluorescent agent. In addition, the content of fluorescent agent is preferably 1% by mass or less, more preferably 0.5% by mass or less, and even more preferably 0.1% by mass or less, calculated based on the oxide of the metal element contained in the fluorescent agent. By making this content content above the lower limit, the fluorescence is not inferior to that of natural human teeth. Furthermore, by making this content content below the upper limit, the reduction in light transmittance and mechanical strength can be suppressed.

[0150] In other words, the content of the fluorescent agent is preferably 0.001% by mass or more and 1% by mass or less, more preferably 0.005% by mass or more and 0.5% by mass or less, and even more preferably 0.01% by mass or more and 0.1% by mass or less.

[0151] In the method for manufacturing a ceramic pre-fired body, after the first heat treatment step, it is preferable to further include a pre-firing step in which a maximum temperature (maximum pre-firing temperature) is maintained at 800°C or higher and 1300°C or lower in an atmosphere with an oxygen partial pressure of 0.12 atm or higher.

[0152] The maximum temperature of the pre-firing process is preferably above 800°C, more preferably above 850°C, even more preferably above 880°C, and especially preferably above 900°C.

[0153] In addition, the maximum temperature of the pre-firing process is preferably below 1300°C, more preferably below 1250°C, even more preferably below 1220°C, and particularly preferably below 1200°C.

[0154] In other words, the maximum temperature of the pre-firing process is preferably above 800°C and below 1300°C, more preferably above 850°C and below 1250°C, even more preferably above 880°C and below 1220°C, and particularly preferably above 900°C and below 1200°C.

[0155] The oxygen partial pressure in the pre-calcination process is preferably 0.12 atm or higher, more preferably 0.15 atm or higher, even more preferably 0.18 atm or higher, and particularly preferably 0.20 atm or higher.

[0156] From the perspective of easily removing combustion residues of organic materials, there are no particular limitations on the atmospheric conditions in the pre-combustion process as long as the oxygen partial pressure is above 0.12 atm. It can be above 0.15 atm, above 0.18 atm, or above 0.20 atm.

[0157] There are no special restrictions on the atmospheric conditions in the pre-firing process; the oxygen concentration under atmospheric conditions can be about 21% (without depressurization or pressurization).

[0158] Regarding the aforementioned atmospheric conditions, nitrogen or other gases can be circulated in an atmosphere with an oxygen concentration of 12% or higher.

[0159] The aforementioned oxygen concentration is preferably 15% or more, more preferably 16% or more, even more preferably 18% or more, and particularly preferably 20% or more.

[0160] As for the aforementioned oxygen concentration, it is acceptable as long as it is below 100%, it can be 100%.

[0161] The holding time of the pre-firing process is not particularly limited as long as the desired ceramic pre-fired body can be produced. It is preferably 1 minute or more, more preferably 2 minutes or more, and even more preferably 5 minutes or more.

[0162] Furthermore, from the viewpoint of minimizing the total time from the start of heating to the end of pre-firing (the time from the start of heating to the end of the holding time at the highest temperature of the pre-firing process), the pre-firing process time is preferably 3 hours or less, more preferably 2 hours or less, and even more preferably 1 hour or less.

[0163] In the method for manufacturing the ceramic pre-fired body of the present invention, after the aforementioned first heat treatment step and before the aforementioned pre-firing step, a second heat treatment step is included to heat the aforementioned molded body.

[0164] In the aforementioned second heat treatment process, from the viewpoint of easily removing combustion residues of organic materials, it is preferable to heat the aforementioned molded body in an atmosphere with an oxygen partial pressure of 0.12 atm or higher.

[0165] The aforementioned second heat treatment step preferably includes a heating step in which the molded body is heated at a heating rate of 2.0°C / minute or higher. The heating step in the aforementioned second heat treatment step can be referred to as the second heating step.

[0166] The heating rate in the aforementioned second heating step is preferably 2.0°C / minute or more. From the viewpoint of suppressing defects and shortening the time until the end of preheating by using a high heating rate, it is more preferably 5.0°C / minute or more, further preferably 10°C / minute or more, particularly preferably 15°C / minute or more, and most preferably 20°C / minute or more.

[0167] The heating rate in the aforementioned second heating step is preferably 1000°C / min or less, more preferably 800°C / min or less, and even more preferably 500°C / min or less.

[0168] In other words, the heating rate in the aforementioned second heating process is preferably 2.0~1000℃ / min, more preferably 5.0~800℃ / min, further preferably 10~500℃ / min, particularly preferably 15~500℃ / min, and most preferably 20~500℃ / min.

[0169] The heating rate in the aforementioned heating process can be constant or varied within the aforementioned range. For example, in the aforementioned heating process, if the rate is 5.0°C / minute or higher, it also includes an implementation where the heating rate starts at 5.0°C / minute and is then changed to 50°C / minute during the process.

[0170] From the viewpoint of suppressing defects and shortening the time until the end of pre-burning by using a high heating rate, the oxygen partial pressure in the aforementioned second heat treatment process is preferably 0.12 atm or more, more preferably 0.15 atm or more, even more preferably 0.18 atm or more, and particularly preferably 0.20 atm or more.

[0171] The temperature range in the aforementioned second heat treatment process is preferably 500°C or higher, more preferably 550°C or higher, even more preferably 580°C or higher, and particularly preferably 600°C or higher.

[0172] In addition, the temperature range in the second heat treatment process is preferably below 1300°C, more preferably below 1250°C, even more preferably below 1220°C, and particularly preferably below 1200°C.

[0173] In other words, the temperature range in the second heat treatment process is preferably 500°C or higher and 1300°C or lower, more preferably 550°C or higher and 1250°C or lower, even more preferably 580°C or higher and 1220°C or lower, and particularly preferably 600°C or higher and 1200°C or lower.

[0174] In addition, as a suitable embodiment, a method for manufacturing a ceramic pre-fired body can be listed, wherein the aforementioned second heat treatment step further includes a holding step of heating the aforementioned molded body by holding it at a constant temperature in the range of 500°C or higher and 1300°C or lower.

[0175] The aforementioned second heat treatment process includes a heating process. By including a holding process at a constant temperature in addition to the heating process, it is possible to suppress the occurrence of defects and effectively degrease, thereby shortening the time until the preheating is completed.

[0176] Regarding the method for manufacturing the ceramic pre-fired body of the present invention, in embodiments excluding the aforementioned holding process, degreasing is performed during the process of heating to the highest temperature of the pre-firing process (highest pre-firing temperature), so degreasing is not omitted.

[0177] On the other hand, as in the aforementioned embodiment, in the second heat treatment step, based on the aforementioned heating step, the aforementioned molded body can be held at a specified temperature and heated. In this embodiment, degreasing can also be performed effectively, the time until the end of pre-firing can be shortened by the high heating rate, and the occurrence of defects can be suppressed.

[0178] There are no special limitations on the temperature in the aforementioned holding process, as long as it is within the temperature range of the second heat treatment process.

[0179] In embodiments that include the aforementioned holding process, the arrival temperature in the first heat treatment process can be set as the holding temperature of the degreasing process.

[0180] In one embodiment including the aforementioned holding process, from the viewpoint of fully degreasing, the arrival temperature in the first heat treatment process is preferably 200°C or higher, more preferably 300°C or higher, and even more preferably 400°C or higher.

[0181] In addition, in one embodiment including the aforementioned holding process, the arrival temperature in the first heat treatment process is preferably lower than the pre-firing temperature, preferably below 650°C, more preferably below 620°C, and even more preferably below 600°C.

[0182] In other words, the arrival temperature in the first heat treatment process is preferably 200°C or higher and 650°C or lower, more preferably 300°C or higher and 620°C or lower, and even more preferably 400°C or higher and 600°C or lower.

[0183] In embodiments having the aforementioned holding process, the second heat treatment process can have a holding process that holds the molded body at the temperature reached by the first heat treatment process (above 500°C) as long as the effects of the present invention are achieved, followed by a heating process, or a heating process can be performed after the first heat treatment process, followed by a holding process that holds the molded body at a specified temperature, and then a heating process.

[0184] In the method for manufacturing the ceramic pre-fired body of the present invention, the total time from the start of the first heat treatment step to the end of the holding time at the highest temperature of the pre-fired step is preferably less than 600 minutes, more preferably less than 300 minutes, further preferably less than 200 minutes, and particularly preferably less than 100 minutes.

[0185] In the method for manufacturing the ceramic pre-fired body of the present invention, the conditions for cooling after the holding time at the highest temperature of the pre-firing process (after the pre-firing process) are not particularly limited, and can be set to the same atmosphere conditions as the pre-firing process.

[0186] The cooling rate is not particularly limited, but is 2.0℃ / minute or more, more preferably 5.0℃ / minute or more, further preferably 10℃ / minute or more, particularly preferably 15℃ / minute or more, and most preferably 20℃ / minute or more.

[0187] The implementation method can be modified, and the cooling rate can be 100℃ / minute or more.

[0188] The method for manufacturing the ceramic pre-fired body used in the present invention is not particularly limited. For example, when the ceramic contains zirconium oxide and a stabilizer (e.g., yttrium oxide), it can be manufactured by the following method.

[0189] A raw material composition containing zirconium oxide powder and a stabilizer is prepared, and the raw material composition is press-molded under a specified pressure to obtain a zirconium oxide molded body.

[0190] The raw material composition is prepared by mixing zirconium oxide powder (e.g., zirconium oxide powder containing monoclinic zirconium as the main component) with a stabilizer powder (e.g., yttrium oxide powder) in such a way that the content of the stabilizer is desired.

[0191] There are no particular limitations on the manufacturing method of zirconia powder. Well-known methods such as crushing and micronizing coarse particles or agglomeration processes that synthesize atoms or ions through nucleation and growth can be used.

[0192] Alternatively, commercially available zirconium oxide powder can be used as the zirconium oxide powder.

[0193] The stabilizer powder (e.g., yttrium oxide powder) can be commercially available, or it can be used after the commercially available powder has been pulverized using a known pulverizing and mixing device (ball mill, etc.).

[0194] Commercially available products include, for example, zirconium oxide powder (trade names "Zpex (registered trademark)" (Y2O3 content: 3 mol%), "Zpex (registered trademark) 4" (Y2O3 content: 4 mol%), "Zpex (registered trademark) Smile (registered trademark)" (Y2O3 content: 5.5 mol%), "TZ-3Y" (Y2O3 content: 3 mol%), "TZ-3YS" (Y2O3 content: 3 mol%), "TZ-4YS" (Y2O3 content: 4 mol%), "TZ-6Y" (Y2O3 content: 6 mol%), "TZ-6YS" (Y2O3 content: 6 mol%), "TZ-8YS" (Y2O3 content: 8 mol%), and "T..." The following are listed: Z-10YS (Y2O3 content: 10 mol%), TZ-3Y-E (Y2O3 content: 3 mol%), TZ-3YS-E (Y2O3 content: 3 mol%), TZ-3YB-E (Y2O3 content: 3 mol%), TZ-3YSB-E (Y2O3 content: 3 mol%), TZ-3YB (Y2O3 content: 3 mol%), TZ-3YSB (Y2O3 content: 3 mol%), TZ-3Y20AB (Y2O3 content: 3 mol%), TZ-8YSB (Y2O3 content: 8 mol%), and TZ-0 (Y2O3 content: 0 mol%). (These are products manufactured by Tosoh Corporation.)

[0195] The aforementioned commercially available zirconium oxide powder also contains HfO2.

[0196] As a commercially available product, zirconium oxide powder containing both zirconium oxide and Y2O3 can also be used.

[0197] As zirconium oxide powder, zirconium oxide powder with Y2O3 dissolved in it can also be uniformly dispersed, as in the aforementioned commercially available TZ series (which includes "TZ" in part of the trade name).

[0198] Zirconia powder, taking into account factors such as crystal system and stabilizer content, can be used alone or in combination with two or more types.

[0199] A mixture of zirconium oxide powder and stabilizer powder is added to water to make a slurry, which is then pulverized (e.g., wet pulverization) to the desired particle size using a pulverizer and mixed.

[0200] The pulverized slurry is dried and granulated. Then, the resulting powder is calcined at a temperature below the sintering temperature of the zirconium oxide particles (e.g., 800~1200℃) to produce a primary powder.

[0201] There are no particular limitations on the pulverizer used for pulverization; any known pulverizer, such as a ball mill, can be used. There are no particular limitations on the drying method for the pulverized slurry; spray drying is preferred.

[0202] There are no particular limitations on spray drying; any known spray dryer can be used.

[0203] The average particle size of the primary powder is not particularly limited, but from the viewpoint of light transmittance of the resulting sintered body, it is preferably 0.2 μm or less.

[0204] It should be noted that the aforementioned average particle size can be determined using laser diffraction scattering. Specifically, the laser diffraction scattering method can be used, for example, with a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation), using a 0.2% sodium hexametaphosphate aqueous solution as the dispersion medium, and measuring the particle size on a volume basis.

[0205] The powder obtained from the above operation is added to water to make a slurry. The slurry is then pulverized (e.g., wet pulverization) to the desired particle size using a grinder and mixed.

[0206] Organic materials (suitable, acrylic binders) are added to the pulverized slurry, and then optional components such as pigments and fluorescent agents are added as needed, followed by drying to produce a secondary powder. The addition of organic materials, etc., is usually after pulverization, but can also be done during or before the pulverization process using a pulverizer.

[0207] The pulverizer and drying method used in the pulverization can be the same as those used to make primary powder.

[0208] The average particle size of the secondary powder is not particularly limited, but from the viewpoint of light transmittance of the resulting sintered body, it is preferably 0.2 μm or less.

[0209] The secondary powder obtained by the above operation is used as the raw material composition. If optional components such as pigments and fluorescent agents are not added during the manufacture of the secondary powder, the aforementioned optional components may be added to the obtained secondary powder.

[0210] The types and contents of ceramics (including the presence of zirconium oxide crystals), the types and contents of stabilizers, and the types and contents of organic materials in the raw material composition are the same as those in the molded body.

[0211] Regarding the content of organic materials, "100% by mass of the total mass of the ceramic molded body" can be understood as "100% by mass of the total mass of the raw material composition".

[0212] Next, the obtained raw material composition is molded to produce a molded body. There are no particular limitations on the molding method, and known methods (such as pressure molding) can be used.

[0213] When manufacturing zirconia molded bodies using a method that includes a step of pressurizing a raw material composition, the specific method of pressurization is not particularly limited, and a known pressurization machine can be used. Examples of specific pressurization methods include, for instance, filling a predetermined mold with the raw material composition and applying uniaxial pressure.

[0214] The pressure is set to an optimal value based on the size, hardness, biaxial bending strength, and particle size of the raw material powder of the target molded body. It is usually above 5 MPa and below 1000 MPa.

[0215] By increasing the pressure applied during molding in the aforementioned manufacturing method, the pores in the resulting molded body are further filled, thereby increasing the density of the molded body. Furthermore, to further increase the density of the resulting zirconia molded body, a cold isostatic pressing (CIP) treatment can be performed after uniaxial pressing.

[0216] The calcining furnace used in the method for manufacturing the ceramic pre-fired body of the present invention is not particularly limited and can be any type of calcining furnace, such as intermittent or continuous operation.

[0217] Examples of intermittent calcining furnaces include intermittent electric furnaces.

[0218] Examples of continuous calcining furnaces include RHK (Roller Hearth Kiln).

[0219] In the method for manufacturing the ceramic pre-fired body of the present invention, the removal of the organic binder in the second heat treatment step and the pre-firing step may include any other conditions such as being carried out in the presence of superheated steam.

[0220] Alternatively, heating water vapor with a temperature difference of about 1~10℃ from the temperature at which the organic binder begins to decompose can be applied to the molded body to inhibit the rapid decomposition of the organic binder.

[0221] On the other hand, by omitting processes such as applying superheated steam to the surface of the molded body, it is possible to manufacture the desired pre-fired ceramic body more easily, and the time from the start of heating to the end of pre-firing (the time from the start of heating to the end of the holding time at the highest temperature of the pre-firing process) can be shortened by using a high heating rate.

[0222] In the method for manufacturing the ceramic pre-fired body described in this invention, the organic components are eliminated through a pre-firing process and / or a second heat treatment process. Therefore, the ceramic pre-fired body does not contain carbon, and the carbon content in the ceramic pre-fired body is less than 0.01% by mass.

[0223] In the method for determining the carbon content in ceramic pre-fired body, the mass of the ceramic pre-fired body before heat treatment (mass before treatment) is measured in the atmosphere, and the mass of the ceramic pre-fired body after heat treatment (mass after treatment) is measured in the atmosphere. The difference between these two measurements is taken as the carbon content contained in the ceramic pre-fired body.

[0224] The heat treatment temperature in the method for determining carbon content is not particularly limited as long as it is the temperature at which the organic material is burned off; for example, it can be set to 700℃.

[0225] The ceramic pre-fired body obtained by the manufacturing method of the present invention can have a specified shape.

[0226] In addition, ceramic pre-fired bodies can have shapes such as discs (round discs), cuboids, or dental products (e.g., crowns).

[0227] The types and contents of ceramics (including the presence of zirconium oxide crystal system) and the types and contents of stabilizers in the ceramic pre-fired body of the present invention are the same as those in the molded body.

[0228] The following explanation of the physical properties of ceramic pre-fired bodies will take zirconia pre-fired bodies containing zirconia as an example.

[0229] Hereinafter, "zirconia pre-sintered body" can be understood as "ceramic pre-sintered body" or "alumina pre-sintered body".

[0230] To ensure sufficient strength for machining, the flexural strength (three-point bending strength) of the zirconia pre-sintered body is preferably 15 MPa or higher. Furthermore, for ease of machining, the flexural strength of the pre-sintered body is preferably 70 MPa or lower, more preferably 60 MPa or lower.

[0231] The aforementioned bending strength was determined according to ISO 6872:2015 (Dentistry-Ceramic materials), with only the dimensions of the test piece changed; a test piece measuring 5mm × 10mm × 50mm was used. The surface of the test piece and its C-surface (obtained by chamfering the corners of the test piece at a 45° angle) were finished along the length using 600-grit sandpaper. The test piece was positioned with the maximum face facing the vertical direction (load direction). In the bending test, the distance between the support points (span) was set to 30mm, and the slider speed was set to 0.5mm / minute.

[0232] The flexural strength of the zirconia pre-fired body can be adjusted according to the pressure applied during the manufacturing process, the content of organic materials (suitable for acrylic binders), the maximum temperature of the pre-firing process, and the holding time at that maximum temperature.

[0233] Regarding the Vickers hardness of the zirconia pre-sintered body, from the viewpoint of abrasiveness, the Vickers hardness is preferably 350 HV 1 / 15 or less, more preferably 300 HV 1 / 15 or less, and even more preferably 100 HV 1 / 15 or less.

[0234] When the Vickers hardness is below 350HV 1 / 15, it exhibits excellent machinability (cutting and grinding properties) and can reduce the rate of chipping.

[0235] "HV 1 / 15" refers to the Vickers hardness when a load (test force) of 1 kgf is applied for 15 seconds.

[0236] The method for determining the Vickers hardness of the zirconia pre-sintered body described in this invention is based on JIS Z 2244:2020.

[0237] The Vickers hardness of zirconia pre-sintered body can be adjusted based on the presence rate of undissolved zirconia stabilizers (e.g., yttrium oxide) in the zirconia pre-sintered body, the density of the pre-sintered body, the average particle size of the particles contained in the pre-sintered body, and the flexural strength of the pre-sintered body.

[0238] From the viewpoint of excellent machinability, the density of the zirconia pre-sintered body described in this invention is preferably 2.7~4.0 g / cm³. 3 More preferably, it is 2.9~3.6 g / cm³. 3 Further preferred values ​​are 3.1~3.4 g / cm³. 3 .

[0239] The density of zirconia pre-sintered body refers to its bulk density.

[0240] The density of the zirconia pre-fired body can be calculated, for example, in the form of (mass of the pre-fired body) / (volume of the pre-fired body). Specifically, the dimensions of the test piece can be accurately measured using a micrometer, the mass of the pre-fired body can be measured using a precision balance, and the density (arithmetic mean of n=3) can be calculated by (mass of the pre-fired body) / (volume of the pre-fired body).

[0241] The density of the zirconia pre-fired body can be adjusted according to the average particle size of the particles contained in the pre-fired body, the content of binder, etc.

[0242] The ceramic pre-fired body (e.g., zirconia pre-fired body) obtained by the manufacturing method of the ceramic pre-fired body described in this invention has a white base tone, excellent light transmittance, and excellent aesthetics. Therefore, it is suitable for use in the manufacture of dental restorations.

[0243] As another embodiment, a method for manufacturing a ceramic sintered body can be listed, which includes a sintering step of holding a pre-fired ceramic body obtained by any of the aforementioned manufacturing methods at a temperature with a maximum calcination temperature exceeding 1200°C and sintering it.

[0244] The ceramic pre-fired body used in the method of manufacturing ceramic sintered body is preferably supplied to, for example, a processing step before the sintering process, so as to use a CAD / CAM (Computer-Aided Design / Computer-Aided Manufacturing) system to machine the disc-shaped ceramic pre-fired body into the shape of a dental article (e.g., a dental crown or other dental patch).

[0245] The atmospheric conditions in the sintering process are the same as those in the pre-firing process.

[0246] The maximum calcination temperature is preferably above 1300°C, more preferably above 1350°C, and even more preferably above 1400°C. Furthermore, the maximum calcination temperature is preferably below 1650°C, more preferably below 1600°C, and even more preferably below 1580°C.

[0247] In other words, the maximum calcination temperature is preferably above 1300°C and below 1650°C, more preferably above 1350°C and below 1600°C, and even more preferably above 1400°C and below 1580°C.

[0248] In the sintering process, the sintering time (holding time) is not particularly limited. From the perspective of being able to obtain the zirconia sintered body as the target with good productivity and stability, the sintering time is preferably 5 minutes or more, more preferably 15 minutes or more, further preferably 30 minutes or more, and preferably 6 hours or less, more preferably 4 hours or less, and further preferably 2 hours or less.

[0249] In other words, the sintering time is preferably 5 minutes or more and 6 hours or less, more preferably 15 minutes or more and 4 hours or less, and even more preferably 30 minutes or more and 2 hours or less.

[0250] According to the present invention, by adjusting the content of monoclinic crystals (e.g., using monoclinic zirconia powder as raw material) and adjusting the proportion of undissolved yttrium oxide (e.g., increasing the mixing ratio of yttrium oxide powder), the reduction in the light transmittance of the produced zirconia sintered body can be suppressed even when the holding time at the highest calcination temperature is short. Furthermore, by shortening the calcination time, production efficiency can be improved and energy costs reduced.

[0251] The heating and cooling rates in the sintering process are preferably set in a way that minimizes the time required for the sintering process. For example, the heating rate can be set according to the performance of the calcining furnace to reach the maximum calcination temperature in the shortest possible time. The heating rate up to the maximum calcination temperature can be set to, for example, 10°C / min or more, 50°C / min or more, 100°C / min or more, 120°C / min or more, 150°C / min or more, or 200°C / min or more. The cooling rate is preferably set at a rate that prevents defects such as cracks from forming in the sintered body. For example, after heating, the sintered body can be allowed to cool naturally at room temperature.

[0252] The zirconia sintered body obtained by calcining the zirconia pre-burnt body of the present invention is suitable for use in dental products.

[0253] Examples of dental products include, for example, inner crowns, frameworks, dental crowns, dental bridges, bridge abutments, implants, implant screws, implant fixation devices, implant bridges, implant bars, dental crowns, dentures, inlays, onlays, orthodontic wires, and veneers.

[0254] By using the zirconia pre-fired body of the present invention for components such as implant screws and implant fixation devices, it is possible to suppress gingival discoloration and achieve excellent aesthetics when using metal materials.

[0255] Furthermore, the manufacturing method can be selected according to the intended use. For example, dental products can be obtained by machining the zirconia pre-sintered body of the present invention followed by sintering. It should be noted that a CAD / CAM system is preferably used in this machining process.

[0256] The relative density of the zirconia sintered body is preferably 99.5% or higher. The relative density can be calculated as the ratio of the measured density, obtained by Archimedes' method, to the theoretical density.

[0257] As long as the effects of the present invention are achieved, the present invention includes various combinations of all or part of the above-described structures obtained within the scope of the technical concept of the present invention. Example

[0258] Next, embodiments are listed to illustrate the present invention in more detail. However, the present invention is not limited to these embodiments at all, and those skilled in the art can make various modifications within the scope of the technical concept of the present invention.

[0259] [Preparation of the raw material composition] The method for preparing the raw material composition used to produce the zirconia molded articles of Examples 1-14 and 16-19 and Comparative Example 1 will be described using Example 1 as an example.

[0260] First, a mixture was prepared using approximately 100% monoclinic zirconia powder and yttrium oxide powder, with the yttrium oxide content relative to the total molar volume of zirconia and yttrium oxide as shown in Table 1. Next, this mixture was added to water to prepare a slurry, which was then wet-milled using a ball mill until the average particle size was below 0.13 μm. A binder (acrylic binder) was added to the pulverized slurry at a content shown in Table 1, within 100% by mass of the total raw material composition, and the slurry was dried using a spray dryer to produce granules (secondary powder). These granules were used as the raw material composition to manufacture the zirconia molded body described later.

[0261] It should be noted that the aforementioned average particle size can be determined using laser diffraction scattering. Specifically, the laser diffraction scattering method can be used, for example, with a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation), using a 0.2% sodium hexametaphosphate aqueous solution as the dispersion medium, and measuring the particle size on a volume basis.

[0262] The resulting primary powder was added to water to prepare a slurry, which was then wet-milled and mixed using a ball mill until the average particle size was below 0.13 μm. A binder (acrylic binder) was added to the pulverized slurry at the percentages listed in Table 1, representing 100% by mass of the total raw material composition. The slurry was then dried using a spray dryer to produce granules (secondary powder). These granules were used as the raw material composition to manufacture the zirconia molded bodies described later.

[0263] In addition, in Examples 15, 2, and 4, instead of monoclinic zirconium oxide powder, a raw material called "Zpex (registered trademark) Smile (registered trademark)" (Y2O3 content: 5.5 mol%) (manufactured by Tosoh Corporation) was used, which is a raw material formed by solidifying yttrium oxide in zirconium oxide.

[0264] In addition, in Comparative Examples 3 and 5, instead of monoclinic zirconium oxide powder, a raw material "TZ-3YS-E" (Y2O3 content: 3 mol%) (manufactured by Tosoh Corporation) was used, which was formed by solidifying yttrium oxide in zirconium oxide.

[0265] [Table 1] .

[0266] It should be noted that the content of each component in Table 1 is as follows.

[0267] The content of NaOH (mol%) and Al2O3 (mol%) are the external addition rates relative to the total 100 mol% of zirconium oxide, Y2O3 and Nb2O5.

[0268] In Table 1, the content of TiO2 (mass%) and the content of colorant (mass%) are external addition rates relative to the total mass% of zirconium oxide, Y2O3 and Nb2O5.

[0269] In Table 1, the Nb2O5 content (mol%) is the content in a total of 100 mol% of zirconium oxide, Y2O3 and Nb2O5.

[0270] The Y2O3 content (mol%) is the content of zirconium oxide, Y2O3, Al2O3 and Nb2O5 in a total of 100 mol%.

[0271] [Fabrication of Zirconia Molded Prototypes] For each embodiment and comparative example, in order to obtain pre-burnt body samples for evaluating fragmentation, crack occurrence and internal residual carbon, a cuboid-shaped molded body is prepared as follows.

[0272] In order to produce a cuboid-shaped molded body, in each embodiment and comparative example, the aforementioned raw material composition particles were fed into a cuboid mold with a length of 19 mm and a width of 20 mm, such that the thickness of the resulting zirconia molded body was 21 mm.

[0273] Next, the raw material composition is pressurized with a surface pressure of 200 MPa using a uniaxial compression molding machine to obtain a rectangular zirconia molded body.

[0274] [Example 1] Using the heating rate, atmosphere conditions, and test furnace recorded in Table 2, the zirconia molded body obtained by the above operation was heated to 600°C.

[0275] Next, the second heat treatment process is carried out at 600°C under the atmosphere conditions and holding time specified in Table 2. After the holding process, the temperature is further increased to 1000°C under the heating rate and atmosphere conditions of the second heat treatment process specified in Table 2.

[0276] Furthermore, 1000℃ was set as the highest temperature for the pre-firing process, and pre-firing was carried out under the atmosphere conditions and holding time recorded in Table 3 to produce a zirconia pre-fired body.

[0277] Figure 1 The changes in oxygen concentration 1 (%) (scale: right side) and temperature 2 (°C) in Example 1 are shown.

[0278] [Examples 2-19 and Comparative Examples 1-5] The conditions for the first heat treatment step, the second heat treatment step, and the pre-firing step are changed to those recorded in Tables 2 and 3. Otherwise, the operation is the same as in Example 1 to produce the zirconia pre-fired body.

[0279] It should be noted that, for Examples 6-15, pre-calcination and degreasing were performed simultaneously.

[0280] [Determination of oxygen concentration and partial pressure] An oxygen sensor (zirconia O2 sensor, trade name "TB-IIF-R", manufactured by Daiichi Thermal Research Co., Ltd.) was installed inside the experimental electric furnace to measure oxygen concentration and oxygen partial pressure.

[0281] Evaluation of fragmentation and cracking in zirconia pre-sintered bodies Ten zirconia pre-fired bodies were manufactured for each embodiment or comparative example, and the presence or absence of fragmentation and cracks on the surface of these zirconia pre-fired bodies was evaluated by visual inspection.

[0282] Even if there is only one, it is evaluated as "present" if there is a chip or crack on the surface, and as "absent" if there is no chip or crack on the surface. The results are shown in Table 4.

[0283] [Evaluation of residual carbon inside the zirconia pre-fired body] Cutting was performed using a surface that passed through the center of the zirconia pre-fired body. The presence of black to gray residual carbon in the center was visually assessed as "present," while the absence of residual carbon was assessed as "absent." The results are shown in Table 4.

[0284] [Evaluation of the pass / fail status of zirconia pre-sintered bodies] An evaluation of "none" in the aforementioned [evaluation of the occurrence of fragmentation and cracks in the zirconia pre-sintered body] and "none" in the [evaluation of residual carbon inside the zirconia pre-sintered body], and a total time from the start of the first heat treatment process to the end of the holding time at the highest temperature of the aforementioned pre-sintering process is less than 800 minutes, is considered "qualified". Otherwise, the evaluation is "unqualified".

[0285] [Table 2] .

[0286] [Table 3] .

[0287] Tables 2 and 3 represent consecutive processes, which should be performed in the order listed in Tables 2 and 3. It should be noted that the meanings of the statements in Tables 2 and 3 are as follows.

[0288] “RHK” refers to a continuous calcining furnace.

[0289] "N2 circulation" refers to the state in which the experimental electric furnace is basically replaced by N2.

[0290] "Atmosphere + N2 circulation" refers to a state where the flow of N2 is low and it is mixed with the atmosphere.

[0291] "N2+ wet circulation" refers to "N2 circulation" that incorporates water vapor.

[0292] "Decompression" refers to using an automatic vacuum-gas replacement furnace (trade name "VF-5000", manufactured by SK Medical Electronics Co., Ltd.) and a vacuum pump to reduce the pressure to about 2 kPa.

[0293] [Table 4] .

[0294] Based on the above results, it can be confirmed that the method for manufacturing the ceramic pre-fired body of the present invention can shorten the time until the end of pre-firing and suppress the occurrence of defects.

[0295] Industrial utilization The method for manufacturing the ceramic pre-fired body of the present invention can significantly shorten the manufacturing process and significantly reduce the manufacturing cost, and is therefore advantageous in industry.

[0296] Explanation of reference numerals in the attached figures 1. Oxygen concentration 2. Temperature.

Claims

1. A method for manufacturing a pre-fired ceramic body, comprising a heat treatment step of heating a shaped ceramic body. The heat treatment process includes a first heat treatment process, and may further include a second heat treatment process as needed. At least one of the first heat treatment step or the second heat treatment step includes a step of heating the ceramic molded body in an atmosphere with an oxygen partial pressure of less than 0.11 atm. The molded body contains organic materials.

2. The method for manufacturing a ceramic pre-fired body according to claim 1, wherein, The first heat treatment process is a heat treatment process conducted in an atmosphere with an oxygen partial pressure below 0.11 atm. The heating rate in the first heat treatment process is 2.0℃ / minute or higher.

3. The method for manufacturing a ceramic pre-fired body according to claim 2, wherein, Following the first heat treatment step, the process further includes a pre-firing step in which the molded body is heated in an atmosphere with an oxygen partial pressure of 0.12 atm or higher, and the maximum temperature is maintained at 800°C or higher and 1300°C or lower.

4. The method for manufacturing a ceramic pre-fired body according to claim 3, wherein, The second heat treatment step is performed after the first heat treatment step and before the pre-firing step. In the second heat treatment process, the molded body is heated in an atmosphere with an oxygen partial pressure of 0.12 atm or higher.

5. The method for manufacturing a ceramic pre-fired body according to claim 4, wherein, The heating rate in the second heat treatment process is 2.0℃ / minute or higher.

6. The method for manufacturing a ceramic pre-fired body according to claim 4 or 5, wherein, The temperature range in the second heat treatment process is above 500°C and below 1300°C.

7. The method for manufacturing a ceramic pre-fired body according to claim 4 or 5, wherein, The second heat treatment process further includes a holding process of heating the molded body by holding it at a constant temperature within a range of 500°C to 1300°C.

8. The method for manufacturing a ceramic pre-fired body according to claim 1 or 2, wherein, The organic material contains an acrylic adhesive.

9. The method for manufacturing a ceramic pre-fired body according to claim 8, wherein, The organic material content is 1 to 12% of the total mass of the ceramic molded body (100% by mass).

10. The method for manufacturing a ceramic pre-fired body according to claim 1 or 2, wherein, The molded body has a diameter exceeding 2.7 cm. 3 A rectangular parallelepiped with a volume and thickness exceeding 1 cm, or having a diameter exceeding 19.0 cm. 3 It is a disc-shaped object with a volume and a thickness of more than 1 cm.

11. The method for manufacturing a ceramic pre-fired body according to claim 1 or 2, wherein, The ceramic contains zirconium oxide and a stabilizer capable of inhibiting the zirconium oxide phase transformation, wherein the zirconium oxide contains monoclinic zirconium oxide as the main component.

12. The method for manufacturing a ceramic pre-fired body according to claim 11, wherein, The stabilizer capable of suppressing the zirconium oxide phase transformation is yttrium oxide, and the ceramic contains yttrium oxide that is not dissolved in zirconium oxide.

13. The method for manufacturing a ceramic pre-fired body according to claim 1 or 2, wherein, The ceramic also contains TiO2.

14. The method for manufacturing a ceramic pre-fired body according to claim 1 or 2, wherein, The ceramic also contains Nb2O5.

15. The method for manufacturing a ceramic pre-fired body according to claim 3, wherein, The pre-firing process takes between 1 minute and 1 hour.

16. The method for manufacturing a ceramic pre-fired body according to claim 3 or 15, wherein, The total time from the start of the first heat treatment step to the end of the holding time at the highest temperature of the pre-firing step is less than 600 minutes.

17. The method for manufacturing a ceramic pre-fired body according to claim 1 or 2, wherein, The pre-fired ceramic body is used to manufacture dental repairs.

18. A method for manufacturing a ceramic sintered body, comprising: a sintering step of sintering a pre-sintered ceramic body obtained by the manufacturing method according to claim 1 or 2 at a temperature with a maximum calcination temperature exceeding 1200°C.

Citation Information

Patent Citations

  • JP1974074705A

  • Ceramic calcined material for cutting and sintering and method for producing the same

    JP2013119485A